Penerapan Dwangsom pada Putusan Hak Asuh Anak Perspektif Teori Keadilan Aristoteles - Muhamad Ali Muhsim; Erfaniah Zuhriah; Ali Hamdan (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
As a result of not implementing the voluntary child custody decision, the next legal remedy is the execution of child custody which can have a negative impact on the child's psyche. As a solution to this problem, the judge can decide on the dwangsom in the child custody decision. However, dwangsom becomes a legal problem when it is not contained in the petitum but appears in the ruling as stated in the decision Number 8/Pdt.G/2020/MS-BNa. The focus of this research is a juridical review and analysis of Aristotle's theory of justice on the application of dwangsom to the decision. This research is a normative juridical research using a law approach and a case approach. The primary legal source is decision Number 8/Pdt.G/2020/MS-BNa. and secondary sources of law, namely laws relating to the procedural law of the Religious Courts, books and journals related to Aristotelian justice, child custody, ultra petita and dwangsom principles. The data of this study were obtained through documentation and analyzed by Aristotle's theory of justice. The results of the juridical review on the decision contradict Article 178 paragraph (3) HIR / Article 189 paragraph (3) RBg, Article 50 Rv, SEMA Decision Number 3 of 2018, and Jurisprudence number 1001 K/Sip/1972. The judge's considerations in deciding the case Number 8/Pdt.G/2020/MS-BNa have met the criteria of Aristotle's corrective justice, namely there is a violation of rights that should be obtained, there are efforts to correct (return) rights, losses can be measured, corrections can be measured, and on a proportional basis.